Employee Retention Strategies Used by Nepalese Banks - Chaudhary, Manoj Kumar (Nepal Journal of Multidisciplinary Research, 2022)
Employee retention has been a key factor for the sustainable operation of any organization. Among all the sectors of an economy, banking sector has been one of the sectors with higher employee turnover. This study aims to investigate retention issues in Civil Bank and Mega Bank limited located in Kathmandu valley. The study has collected data from 132 employees (from different levels and different departments working in these commercial banks through 5-point Likert questionnaire and processed with the help of SPSS. The collected data are analyze using descriptive statistics and regression analysis. The study results show that workplace environment, career growth & development opportunity, compensation management and job security have significant impact and association with the employee’s retention in Civil Bank and Mega Bank located in Kathmandu. It is recommended that plan for work life balance and better career planning for the employees could increase to establishing the stability of employees working in banking sectors.